2010
DOI: 10.1111/j.1469-0691.2009.03080.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping analyses of tuberculosis transmission among immigrant residents in Italy

Abstract: We used DNA fingerprinting to analyse tuberculosis (TB) epidemiology in immigrant patients living in two major northern Italian urban areas. The study population included 1999 TB patients (1500 Italian-born and 499 immigrants). Univariate and multivariate logistic regression models were used to identify risk factors related to clustering similar proportions of immigrant and Italian-born patients (46%) had infection with TB strains that belonged to genetic clusters. This supports the hypothesis that the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…In general, TB in immigrant populations in lowendemicity settings is thought to result mostly from reactivation of infection acquired prior to or shortly after immigration (435,(437)(438)(439). Also, the studies described above have shown that urban settings are a risk factor for TB transmission (445).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
See 1 more Smart Citation
“…In general, TB in immigrant populations in lowendemicity settings is thought to result mostly from reactivation of infection acquired prior to or shortly after immigration (435,(437)(438)(439). Also, the studies described above have shown that urban settings are a risk factor for TB transmission (445).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
“…Here too, the clustering rate was significantly higher among the homeless population; by multivariate analysis, homelessness, male sex, an age of Ͻ40 years, the presence of pulmonary TB, work as a day laborer or unemployment, and being born in Japan were all associated with clustering, as was disease caused by Beijing genotype strains (438). In two urban areas in Northern Italy (Milan and Brescia), a 7-year population-based study showed that risk factors for strain clustering included an immigrant status, particular nationalities (Somali, Senegalese, or Peruvian), and city of residence: clustering was more frequent among immigrants with TB in Milan than in Brescia (49% versus 31%) (439). In Alabama, risk factors for clustering on the basis of recent transmission were young age, homelessness, alcohol abuse, urban residency, history of imprisonment, and black race but not HIV infection (440); HIV infection was a risk factor for recent transmission in an earlier study in San Francisco, along with being born in the United States, substance abuse, and homelessness.…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
“…The importance of TB contact locations such as community drop-in centers, bars, and parks, and social networks have been explored to great effect (Cook et al, 2007;Carter et al, 2009). Indeed, the movements of people in space and migrants, in particular, have contributed to the spread of TB in both developing (Long et al, 2008;Wei et al, 2009;PaceAsciak et al, 2013) and developed countries (Haase et al, 2007;McPherson et al, 2008;Franzetti et al, 2010;Edelson and Phypers, 2011). An earlier study by Jia et al (2008) reported a higher rate of TB prevalence in migrants than the local residents of Beijing.…”
Section: Tuberculosismentioning
confidence: 99%
“…Given that the majority of active TB in foreign-born persons in low-incidence countries arises from reactivation of LTBI, acquired many years previously in the country of origin, as also demonstrated by epidemiological studies based on M. tuberculosis strain isolates by molecular genotyping that found that 55-90% of TB cases in foreign-born persons are due to LTBI reactivation [40][41]. Screening new entrants for LTBI remains the cornerstone for controlling imported TB.…”
Section: Management Of Ltbi Among Immigrants and Screening Practicesmentioning
confidence: 99%